2007
DOI: 10.1177/0731684407079515
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Behavior of Laminated Composite Plates

Abstract: In this study, the influence of boundary conditions on the buckling load for rectangular plates of various cutout shape, length/thickness ratio, and ply orientation is examined. Boundary conditions consisting of clamped, pinned, and their combinations are considered. Numerical and experimental studies are conducted to investigate the effect of boundary conditions, cutout shape, length/thickness ratio, and ply orientation on the buckling behavior of E-glass/epoxy composite plates under in-plane compression load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 13 publications
(19 reference statements)
1
24
0
1
Order By: Relevance
“…Baba [19] and Baba and Baltaci [20] studied the effect of support conditions on the buckling load laminated plates with circular in semicircular cutouts under axial compression. They found that the buckling load of clamped-clamped plates is 75% higher than the buckling load of simply supported plates, and 50% for the case of clamped-pinned boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…Baba [19] and Baba and Baltaci [20] studied the effect of support conditions on the buckling load laminated plates with circular in semicircular cutouts under axial compression. They found that the buckling load of clamped-clamped plates is 75% higher than the buckling load of simply supported plates, and 50% for the case of clamped-pinned boundary condition.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout operation the composite laminate plates are generally subjected to compression loads that may basis buckling if overloaded. Consequently their buckling behaviors are significant factors in safe and reliable design of these structures [3]. For predicting the buckling load and buckling mode form of a structure in the finite element program, the linear (or eigenvalue) buckling analysis is an existing technique for estimation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The thin walled composite structures which are widely used become unstable when they are subjected to mechanical or thermal loads leading to buckling. Accordingly, their behaviors in buckling are significant factors in safe and reliable design (Baba, 2007). Baba and Baltaci (2007) have performed a buckling analysis of a laminated composite rectangular plate having a circular hole at the center.…”
Section: Introductionmentioning
confidence: 99%